Corporate Social Responsibility dan Profitabilitas dalam Mempengaruhi Praktik Penghindaran Pajak pada PT. Bank Rakyat Indonesia (Persero) - Wahyuliza, Suci; Rahmansyah, Yudhi (Jurusan PIPS FKIP UMMY Solok, 2020)
This study aims to determine the effect of Corporate Social Responsibility and company profitability on tax avoidance practices at PT. Bank Rakyat Indonesia (Persero). The approach taken in this research is a quantitative descriptive approach. Data collection techniques in this study are to use documentation techniques and literature study. Meanwhile, the analysis technique used is multiple linear regression, classical assumption test, hypothesis test (t test, f test) and the coefficient of determination. Based on multiple linear regression analysis, Tax Avoidance Practices are obtained of 0.669, which means that if CSR and Profitability do not exist or are equal to zero, then Tax Avoidance Practices are 0.225. Partially, CSR (X1) and Profitability (X2) have a significant effect on Tax Avoidance Practices (Y). Simultaneously, CSR (X1) and Profitability (X2) together have a significant effect on Tax Avoidance Practices (Y).